从《新兵正传》电影系列的字幕翻译探讨新加坡的文化意涵 = A study on Singapore’s culture based on the translated subtitles in the “Ah Boy’s to Men” movie series - 叶方婷 Yip, Geralyn Fong Ting (2019)
《新兵正传》系列是由新加坡导演梁智强执导及编剧的电影系列。这一系列迄今已拍摄四个单元，分别是《新兵正传1》(2012)、《新兵正传2》(2013)、《新兵正传3: 蛙人传》(2015) 与《新兵正传4》(2017)。第一部、第二部获得 2012、2013年新加坡电影最高票房纪录，而第三部也成为2015年本地十大电影票房之一。事实上，这也是他至今最成功的作品。《新兵正传》系列展现新加坡军队一般市民及观影者难以看到的新加坡军事训练情形，电影也展示了军人同胞之间的友谊、摩擦，以及军人与家人朋友之间的复杂却感人的亲情、友情与爱情。四部电影的内容也有不同之处，如《新兵正传 1》与《新兵正传 2》述说的是新兵在基本军训中的过程，而《新兵正传 3：蛙人传》的内容围绕着海军军训，《新兵正传4》的内容则围绕着预备役军训。四部电影虽各有不同，但无论重点如何，电影的难得可贵之处，除了在内容本身，也在字幕上，因为梁智强的电影一向有极大的文化共融能力，即吸引不同宗族的观众，也在国外大受欢迎。要让本地观众观察明白富有特色的军训文化，要让国际观众明白新加坡本地用语，我们一定要深入这电影系列的字幕，特别是其文化内涵。与此同时，论文也会探讨《新兵正传》电影系列如何受到文化因素限制，影响到这些翻译字幕的文本结构及安排。The “Ah Boys to Men” movie series is directed by well known Singapore producer and director， Jack Neo. Till today, there have already been four “Ah Boy to Men” series that were shot and produced. These include “Ah Boys to Men 1” (2002), “Ah Boys to Men 2” (2013), “Ah Boys to Men 3: Frogmen” (2015) and lastly, “Ah Boys to Men 4” (2017). The movie series was very well-acclaimed and the first two series achieved the reputations of being the highest grossing film in Singapore in 2012 and 2013 respectively. Apart from that, “Ah Boys to Men 3: Frogmen” (2015) also ranked as one of the top ten grossing films in Singapore in 2015. To date, this movie series is also Jack Neo’s most successful movie production. In the “Ah Boys to Men” movie series, it features the Singapore military training scenarios and procedures which commoners are very unlikely to see in real life. Apart from the military training featured predominantly in the movie series, the movie series also has many touching plots revolving around soldier brotherhood, family relationships and romantic relationships. Furthermore, the content of these four different series are also different as “Ah Boys to Men 1” (2002) and “Ah Boys to Men 2” (2013) feature the life of new National Service soldiers in basic military training, while “Ah Boys to Men 3” (2015) shows the life of soldiers in the navy and “Ah Boys to Men 4” (2017) shows soldiers in reservist training. Although these four series may have different contents, the subtitles in the series have the equal importance. This is because many of Jack Neo’s films are watched by audiences of different cultural backgrounds as well as those from overseas. To help these audiences understand Singapore’s military culture and Singapore’s language use with regards to culture, it is important to analyse the subtitles of this movies series, especially its cultural aspects. In addition, this report will also analyse how the movie series’ subtitles have been affected by cultural influences and aspects, with regards to its structure, form, use of words etc.